All-terrain vehicle–related injuries and deaths in Newfoundland and Labrador between 2003 and 2013: a retrospective trauma registry review. Issue 2 (11th July 2017) - Black, Holly; Whalen, Desmond; Alani, Sabrina; Rogers, Peter; MacLean, Cathy
Abstract: Background: Injury and death involving all-terrain vehicles (ATV) has been reported in a number of Canadian provinces. The objective of this study is to describe the frequency, nature, severity, population affected, immediate health costs, efficacy of related legislation, and helmet use in ATV related injuries and deaths in Newfoundland and Labrador (NL). Methods: A retrospective review of injured or deceased ATV riders of all ages entered in the Newfoundland and Labrador Trauma Registry from 2003 to 2013 was conducted. Variables studied included demographics, injury type and severity, use of helmets, admission/discharge dates, and referring/receiving institution. Data was also obtained from the Newfoundland and Labrador Center for Health Information (NLCHI) and included all in-hospital deaths and hospitalizations due to ATVs between 1995 and 2013. Results: There were a total of 298 patients registered in the trauma registry, resulting in 2759 admission days, nine deaths, and a total estimated immediate healthcare system cost in excess of 1.6 million. More males (N=253, 84.9%) than females (N=45, 15.1%) were injured in ATV related incidents, t(20)=7.12, p<.0001. Head and thorax injuries were the most serious. 38.6% of patients were confirmed to be wearing helmets. Mean injury severity scores are as follows: head injury (M=11, SD=9.51), thorax (M=10, SD=8.3), abdominal/pelvis (M=9, SD=7.62), upper extremity (M=9, SD=8.53), other injuries (M=9, SD=10.56) lower extremity (M=8, SD=8.34), and spine (M=8, SD=6.52). Conclusions: This study describes ATV related injuries and deaths in NL. Information from this study may guide physician practice, public education, and future legislation. RÉSUMÉ: Introduction: Des blessures et des décès liés aux accidents de véhicule tout-terrain (VTT) sont déclarés dans différentes provinces au Canada. L'étude visait à décrire la fréquence, la nature et la gravité des blessures liées aux accidents de VTT à Terre-Neuve-et-Labrador (T.-N.-L.), de même que la mortalité, la population touchée, les coûts directs en soins de santé, l'efficacité des lois en la matière et le port du casque de protection. Méthode: Il s'agit d'un examen rétrospectif de dossiers d'utilisateurs de VTT de tous âges, morts ou blessés dans des accidents de ce type de véhicule, et inscrits dans le Newfoundland and Labrador Trauma Registry, de 2003 à 2013. Différentes variables ont été examinées, notamment des données démographiques, le type de blessure et la gravité des lésions, le port du casque, les dates d'admission et de sortie ainsi que les établissements d'origine et d'accueil. Des données ont également été obtenues du Newfoundland and Labrador Center for Health Information et elles comprenaient toutes les hospitalisations ainsi que tous les décès survenus à l'hôpital, attribuables aux accidents de VTT et enregistrés entre 1995 et 2013. Résultats: Au total, 298 patients ont été inscrits dans le registre des traumas; les accidents se sont soldés par 2759 jours d'hospitalisation et 9 décès, ce qui a entraîné un total estimé de plus de 1, 6 million de dollars en coûts directs pour le système de santé. Plus d'hommes (N=253; 84, 9 %) que de femmes (N=45; 15, 1 %) ont été blessés dans des accidents mineurs et majeurs de VTT (t[20]=7, 12; p <0, 0001). Les accidents les plus graves touchaient la tête et le thorax. Un certain nombre de patients, soit 38, 6 %, portaient un casque. Le score moyen de la gravité des blessures s'établissait comme suit : le crâne (M=11, écart-type [σ]=9, 51), le thorax (M=10, σ=8, 3), l'abdomen et le pelvis (M=9, σ=7, 62), les membres supérieurs (M=9, σ=8, 53), d'autres types de blessure (M=9, σ=10, 56), les membres inférieurs (M=8, σ=8, 34) et la colonne vertébrale (M=8, σ=6, 52). Conclusions: L'étude a permis de décrire les différents types de blessure liés aux accidents de VTT et les décès qui en découlent à T.-N.-L. L'information ainsi obtenue peut imprimer une orientation à la pratique médicale, à l'éducation du public et aux lois futures.